Exit Spirals in Hospital Clinics: Conceptualizing Turnover Contagion Among Nursing Staff - Selberg, Rebecca; Mulinari, Paula (Scandinavian Journal of Public Administration, 2022)
This article introduces the concept of the exit spiral to conceptualize processes in which poorly functioning hospital clinics or wards enter a phase of decline due to widespread dissatisfaction among staff, prompting turnover contagion. In describing and analyzing cases amassed during observations and interviews, the article provides tools to identify, analyze and halt exit spirals. Once a hospital ward finds itself in an exit spiral, employees experience increased workloads, loss of control and discontent. Managers may react with increased rigidity. Instability, discontinuity, and insufficient knowledge transfer are processes sparked by exit spirals. The article suggests that exit spirals can be halted if management recognizes the depth of organizational decline and directs resources to resolve it. This requires further analysis, stimulation of employee voice, innovation, and flexibility.